2004
DOI: 10.1002/jez.a.20018
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation effects on anhydrobiotic survival in the tardigrade Richtersius coronifer

Abstract: For anhydrobiotic metazoans the rate of desiccation is an important factor influencing the probability of survival in a dry anhydrobiotic state. Formation of animal aggregations, in which the exposed body surface area of individual animals is reduced, represents one way to reduce the rate of evaporation. Such aggregations have earlier been documented in e.g., nematodes. We experimentally evaluate the effect of aggregation size (number of animals in a group of desiccating animals) on anhydrobiotic survival in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…In arthropods, aggregation behavior is often seen to lower susceptibility to dehydration as it reduces the body surface area exposed to the air (Allee, 1926 ; Broly et al, 2013 ) and can create a local microclimate of increased humidity for all group individuals, thus decreasing the water loss rate (Schliebe, 1988 ; Yoder et al, 2002 ). This has been verified in a variety of organisms where positive effects of group size were found in terms of reduced weight and water loss and increased survival (Glass et al, 1998 ; Ivarsson and Jonsson, 2004 ; Rojas et al, 2013 ). This can be particularly relevant for several social spider species (including S. dumicola ) as they inhabit periodically arid areas.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In arthropods, aggregation behavior is often seen to lower susceptibility to dehydration as it reduces the body surface area exposed to the air (Allee, 1926 ; Broly et al, 2013 ) and can create a local microclimate of increased humidity for all group individuals, thus decreasing the water loss rate (Schliebe, 1988 ; Yoder et al, 2002 ). This has been verified in a variety of organisms where positive effects of group size were found in terms of reduced weight and water loss and increased survival (Glass et al, 1998 ; Ivarsson and Jonsson, 2004 ; Rojas et al, 2013 ). This can be particularly relevant for several social spider species (including S. dumicola ) as they inhabit periodically arid areas.…”
Section: Introductionmentioning
confidence: 83%
“…Clustering of individuals is an important behavioral adaptation for arthropods that are either susceptible to water loss due to high evaporation rates and/or that inhabit arid environments. Indeed, several studies reveal a lower weight loss rate (snails, Rojas et al, 2013 ; woodlice, Broly et al, 2014 ), water loss rate (dust mites, Glass et al, 1998 ; bed bugs, Benoit et al, 2007 ) and higher survival (Ivarsson and Jonsson, 2004 ) in larger groups compared to solitary individuals under desiccation stress. Aggregation in clusters reduces the body surface area exposed to the air (Allee, 1926 ; Broly et al, 2014 ) and can create a local microclimate of increased humidity for all individuals in the group (Schliebe, 1988 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that the ability to survive desiccation was highly correlated with the bdelloids aggregating together. This aggregation phenomenon had already been observed in desiccation‐resistant tardigrades and nematodes and was described as a way to reduce the evaporation rate by reducing exposed body surface area (Ivarsson & Jönsson, ). Clusters of A. vaga individuals were already present 15 h through the dehydration process, when agarose was still hydrated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on desiccation tolerance have focused on various invertebrates, including nematodes, rotifers and the brine shrimp, Artemia salina 30 32 . Within tardigrades focus has been on semi-terrestrial species 13 15 , 17 , 19 , 20 , 22 , 33 , 34 , and little is known of desiccation tolerance in marine tardigrades 23 , 24 . In the current study we investigate desiccation tolerance in the marine tidal cosmopolitan, Echiniscoides sigismundi , a species that belongs to the poorly studied heterotardigrade lineage.…”
Section: Discussionmentioning
confidence: 99%